1996
DOI: 10.1083/jcb.133.6.1217
|View full text |Cite
|
Sign up to set email alerts
|

Annexin II in exocytosis: catecholamine secretion requires the translocation of p36 to the subplasmalemmal region in chromaffin cells.

Abstract: Abstract. Annexin II is a Ca2+-dependent membranebinding protein present in a wide variety of cells and tissues. Within cells, annexin II is found either as a 36-kD monomer (p36) or as a heterotetrameric complex (p90) coupled with the S-100-related protein, pll. Annexin II has been suggested to be involved in exocytosis as it can restore the secretory responsiveness of permeabilized chromaffin cells. By quantitative confocal immunofluorescence, immunoreplica analysis and immunoprecipitation, we show here the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
104
1
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 77 publications
(104 reference statements)
5
104
1
6
Order By: Relevance
“…Immunocytochemistry-Transfected PC12 and chromaffin cells were washed twice with Locke's solution and then incubated for 10 min either in calcium-free Locke's solution (resting conditions) or in Locke's solution containing a depolarizing concentration of potassium (stimulation) before the fixation step and further processed for immunofluorescence as described previously (12,19). The primary antibodies were used at the following dilutions: anti-GH antibody (1/150) and anti-SNAP25 antibody (1/200).…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemistry-Transfected PC12 and chromaffin cells were washed twice with Locke's solution and then incubated for 10 min either in calcium-free Locke's solution (resting conditions) or in Locke's solution containing a depolarizing concentration of potassium (stimulation) before the fixation step and further processed for immunofluorescence as described previously (12,19). The primary antibodies were used at the following dilutions: anti-GH antibody (1/150) and anti-SNAP25 antibody (1/200).…”
Section: Methodsmentioning
confidence: 99%
“…and in the subcortical region. Recently, we suggested that the translocation of p36 may be an early event in the process of regulated exocytosis and that translocation of p36 to the cell periphery may precede the phosphorylation process (Chasserot-Golaz et a!., 1996). It will be important to analyze the relationship between the phosphorylation and the translocation steps, especially in view of the postulated role of annexin 2 in catecholamine secretion.…”
Section: P0mentioning
confidence: 99%
“…This protein can partially restore Ca2+-dependent secretory activity in digitonin/SLOpermeabilized chromaffin cells, and annexin II can aggregate chromaffin granules at Ca2+ concentrations in the ,tM range (Ali et al, 1989;Drust and Creutz, 1988;Sarafian et al, 1991;Chasserot-Golaz et al, 1996). In the endocytic pathway, immunoelectron microscopic studies have shown that annexin II is associated with plasma membrane and early endosomes of BHK cells and with the apical and basolateral plasma membranes and early endosomes of polarized MDCK cells (Harder and Gerke, 1993).…”
Section: Introductionmentioning
confidence: 99%